Arcuate NPY is involved in salt‐induced hypertension via modulation of paraventricular vasopressin and brain‐derived neurotrophic factor. Issue 5 (21st March 2022) - Zhang, Chen‐Liang; Lin, Yi‐Zhang; Wu, Qi; Yan, Chenxu; Wong, Matthew Wai‐Kin; Zeng, Fan; Zhu, Ping; Bowes, Kelsey; Lee, Kailun; Zhang, Xuan; Song, Zhi‐Yuan; Lin, Shu; et al.
Abstract: Chronic high salt intake is one of the leading causes of hypertension. Salt activates the release of the key neurotransmitters in the hypothalamus such as vasopressin to increase blood pressure, and neuropepetide Y (NPY) has been implicated in the modulation of vasopressin levels. NPY in the hypothalamic arcuate nucleus (Arc) is best known for its control in appetite and energy homeostasis, but it is unclear whether it is also involved in the development of salt‐induced hypertension. Here, we demonstrate that wild‐type mice given 2% NaCl salt water for 8 weeks developed hypertension which was associated with marked downregulation of NPY expression in the hypothalamic Arc as demonstrated in NPY‐GFP reporter mice as well as by in situ hybridization analysis. Furthermore, salt intake activates neurons in the hypothalamic paraventricular nucleus (PVN) where mRNA expression of brain‐derived neurotrophic factor (BDNF) and vasopressin was found to be upregulated, leading to elevated serum vasopressin levels. This finding suggests an inverse correlation between the Arc NPY level and expression of vasopressin and BDNF in the PVN. Specific restoration of NPY by injecting AAV‐Cre recombinase into the Arc only of the NPY‐targeted mutant mice carrying a loxP‐flanked STOP cassette reversed effects of salt intake on vasopressin and BDNF expression, leading to a normalization of salt‐dependent blood pressure. In summary, our study uncovers an important Arc NPY‐originated neuronal circuitry that could sense and respond to peripheral electrolyte signals and thereby regulate hypertension via vasopressin and BDNF in the PVN.